Cellulose Nanocomposite Fabrics with In-situ Generated Copper Oxide Nanoparticles Using Aquilaria Malaccensis (Agarwood) Leaf Extract as the Reducing Agent - Sathia Lingam, Valan; De Cruz, Alice Escalante; Jacob, Patricia Jayshree; Sinouvassane, Djearamane (INTI International University, 2022)
Metallic nanoparticles often agglomerate when used as fillers in different matrices. In-situ generation of the nanoparticles in the matrices is suggested to overcome this problem. The present study aimed to use Aquilaria malaccensis leaf extract to synthesize copper oxide nanoparticles (CuONPs) on a cellulose cotton fabric. A surface coating of copper oxide was in-situ synthesized on the surface of cotton fabric using A. malaccensis leaf extract. Characterization of the copper oxide nanoparticle composite fabrics (CNCFs) was conducted using FESEM-EDX, and its antibacterial potential was assessed. The CuONPs formed on the surface of the cotton fabric were mainly spherical, ranging from 5 to 27 nm. The CNCFs exhibited good antibacterial activity against Escherichia coli and Bacillus subtilis, evaluated after 24 hours of incubation. Comparative CuSO4-embedded fabrics showed lower antimicrobial inhibition. The CNCFs prepared using this environmentally friendly method showed prominent antibacterial properties and can be considered for medical and packaging applications.